EVERYONE SHOULD DO THEIR BIT TO UPLIFT USM’S NAME, URGES DATUK DR. CHAMIL WARIYA - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 23 March 2016 Universiti Sains Malaysia (USM) should share its successes continuously through the various media available, be they traditional or new, to increase its visibility to the public.